(untitled) (International Seven Journal of Health Research, 2024)
Introduction: Between 2015 and 2016, Brazil experienced an increase in cases of microcephaly in newborns, during an epidemic of Zika Virus (ZIKV) - a Flavivirus discovered in 1947 in the Zika forest, Uganda. During this period, the relationship between ZIKV contamination during pregnancy and severe congenital brain alterations in newborns was confirmed. The consequences of this correlation were profound, affecting families and communities and requiring a significant mobilization of resources and support for the care and development of affected children. Objective: The general objective of this study is to associate ZIKV infection with congenital neurological disorders. Methodology: This consists of an analytical review of the literature, based on scientific articles and secure databases such as SciELO, PubMed, Google Scholar and the Ministry of Health. In addition to a technical visit for a scientific basis with a professional in the field, as well as a social intervention, developed for the guidance of pregnant women, through an informative folder. Development: Among the neurological risks deleterious to the fetus during development, microcephaly proved to be the most obvious sign among affected children, related to the capacity for transplacental dissemination and the apoptotic mechanism of embryonic cells. Among the affected population, there was a higher incidence in the Northeast region, among single mothers, aged over 30, with low schooling, self-declared black, with low income and living in areas with less public policy coverage. In addition, among the outcomes, death among the affected newborns averaged 1.4 months, as well as prematurity and low birth weight, linking nutritional and health conditions with social factors. In addition, it was noted that alterations in neonates were sometimes only detected after birth and diagnosis was made difficult at the start of the epidemic. However, the impact of coping with the disease was not only integral to the children, but also to the families affected, highlighting the need for support and the imperative of educational actions aimed at protecting against the virus. Final considerations: From the above, it was concluded that the neurological risks in neonates resulting from ZIKV were associated with a triad of aspects: sociodemographic and environmental conditions facilitated the rapid spread of the virus, especially among the population with greater social vulnerabilities, triggering neurological damage to developing fetuses, especially in the first trimester of pregnancy. Prevention stands out as one of the most important forms of health action to combat the proliferation of this virus.